Perbandingan Hasil Penerjemahan Buku Cerita Anak-Anak Dongeng Danau Toba dari Bahasa Indonesia ke Bahasa Inggris Melalui Penerjemah dan Mesin Penerjemah - Suprato, Djuria (Bina Nusantara University, 2014)
Machine translation is one of the technological advances that can help the translator to do the translation functions easier and faster. The purpose of this article is to analyze whether the machine translation can be relied upon as a substitute translator. From the analysis, it can be concluded that the existing machine translation cannot replace a translator because of its limitations, especially on understanding the context and cultural situation in a nation. Therefore, this machine is only in assisting the process of translation. The method used is the literature analysis. It analyzes the book translated by translator and translated by translation machine and it turns out that the book translated by a machine is not accurately comprehended.